Clay Attenuates Diarrhea Induced by Fat in a Mouse Model - Shalom Emmanuel; Nyma Siddiqui; Ting Du; Eric Asare; Yuan Chen; Huan Xie; Dong Liang; Song Gao (Metabolites, 2025)
Background: Diarrhea induced by an excessive amount of fat is a prevalent gastrointestinal disorder. Currently, there are limited animal models and treatment options for diarrhea associated with fat. This study aims to develop a mouse model of high-fat-associated diarrhea using glyceryl-trioleate (GTO) and evaluate the potential of montmorillonite clay (MMT) in mitigating this condition. Methods: GTO was administered to mice at different doses through oral gavage to induce diarrhea. Clay was treated through oral gavage to evaluate its anti-diarrhea effect. Fecal conditions were monitored. Intestinal tissues were subjected to histological examination to assess structural integrity. The total fecal bile acids were evaluated using a bile acid assay kit to determine the mechanism of action. Results: The results showed that a diarrhea model was established by administering GTO at 2000 mg/kg. When the animals were treated with clay, diarrhea incidence and severity were decreased significantly in a dose-dependent manner. Compared to the untreated group receiving GTO alone, clay co-administration at 2000 mg/kg reduced diarrhea scores by approximately 48%, while the higher dose of 4000 mg/kg achieved an 83% reduction. Fecal bile acid analysis showed that diarrhea is associated with total bile acid levels in the feces. Histological exams showed that diarrhea is associated with tissue inflammation in the colon. Conclusions: This study showed that GTO administration induced diarrhea in mice, and clay effectively alleviates fat-induced diarrhea through modulation of fecal bile acid composition. These findings suggest that this model can be used to evaluate diarrhea associated with excessive amounts of fat and clay that can be further tested for diarrhea attenuation.